2016
DOI: 10.1080/00914037.2016.1163570
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an S-nitroso-N-acetylpenicillamine–based nitric oxide releasing polymer from a translational perspective

Abstract: Due to the role of nitric oxide (NO) in regulating a variety of biological functions in humans, numerous studies on different NO releasing/generating materials have been published over the past two decades. Although NO has been demonstrated to be a strong antimicrobial and potent antithrombotic agent, NO-releasing (NOrel) polymers have not reached the clinical setting. While increasing the concentration of the NO donor in the polymer is a common method to prolong the NO-release, this should not be at the cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
131
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 64 publications
(147 citation statements)
references
References 50 publications
14
131
2
Order By: Relevance
“…The incorporation of SNAP in medical grade polymers have been shown to be hemocompatible and possesses stability during long-term storage at room temperature and physiological conditions [63, 72, 73]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of SNAP in medical grade polymers have been shown to be hemocompatible and possesses stability during long-term storage at room temperature and physiological conditions [63, 72, 73]. …”
Section: Resultsmentioning
confidence: 99%
“…Another report has also shown that hydrophobic polymers with SNAP have extended NO-release at physiological levels (up to 20 days) [70]. Furthermore, the incorporation of SNAP in medical grade polymers are not only hemocompatible and biocompatible but also stable during long-term storage (6 months) at room temperature [63, 72, 73]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35, 4161 It is a free radical that reacts with superoxides and oxygen to form peroxynitrite and dinitrogen trioxide, respectively. 42, 43, 62 Nitric oxide’s mechanisms of action against bacteria include nitrosation of amines and thiols in the extracellular matrix, lipid peroxidation and tyrosine nitration in the cell wall, and DNA cleavage in the cellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Many NO donors such as S -nitrosothiols [33, 34] and N-diazeniumdiolates [35, 36] have been developed and studied for their potential to locally release NO from polymer surfaces. The addition of NO donors into polymeric materials has been shown to be non-cytotoxic and non-hemolytic, while maintaining the mechanical properties of the base polymer [37]. …”
Section: Introductionmentioning
confidence: 99%